2020
DOI: 10.2147/dmso.s238990
|View full text |Cite
|
Sign up to set email alerts
|

<p>Comparison of the Value of Neutrophil to High-Density Lipoprotein Cholesterol Ratio and Lymphocyte to High-Density Lipoprotein Cholesterol Ratio for Predicting Metabolic Syndrome Among a Population in the Southern Coast of China</p>

Abstract: Background: This study aimed to determine the optimal cutoff values and evaluate the associations of neutrophil to high-density lipoprotein cholesterol ratio (NHR) and lymphocyte to high-density lipoprotein cholesterol ratio (LHR) with metabolic syndrome (MetS), stratified by sex. Methods: A large-scale cross-sectional survey was conducted among 1401 adults from January to April 2018 in six communities in Wanzhai Town, Zhuhai City, on the southern coast of China. Receiver operating characteristics (ROC) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…They also concluded that LHR may be a useful marker of inflammation to assess the presence and severity of MetS (16). Similarly, Tong Chen and colleagues revealed that both LHR (OR: 3.671) and neutrophil to high-density lipoprotein cholesterol ratio (NHR) (OR: 1.728) can predict MetS in females only independent of associated risk factors (17). In consistent with previous studies, data from our study also found that increasing value of LHR was correlated with higher risk of MetS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also concluded that LHR may be a useful marker of inflammation to assess the presence and severity of MetS (16). Similarly, Tong Chen and colleagues revealed that both LHR (OR: 3.671) and neutrophil to high-density lipoprotein cholesterol ratio (NHR) (OR: 1.728) can predict MetS in females only independent of associated risk factors (17). In consistent with previous studies, data from our study also found that increasing value of LHR was correlated with higher risk of MetS.…”
Section: Discussionmentioning
confidence: 96%
“…Hemogram parameters, like lymphocyte, platelet count, and biochemical indexes, like HDL-C, LDL-C, were reported to be markers of inflammation. Lymphocyte to high-density lipoprotein cholesterol ratio (LHR) and platelet to lymphocyte ratio (PLR), as a novel inflammatory marker, were proved to be associated with many cardiovascular risk factors (13)(14)(15)(16)(17). To the best of our knowledge, there was no studies aiming to assess the possible predictive effect of LHR and PLR on newly diagnosed MetS among rural subjects from Northeast China.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as regards the complex interaction between neutrophils and HDL-C, a comprehensive indicator of NHR may be more effective and reliable than a single indicator. In previous studies, NHR was calculated as a simple ratio of neutrophils and HDL-C, and related reports have assessed them as predictive markers of metabolic syndrome [ 23 ]. Another study showed a correlation between NHR and the extent of coronary artery disease [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigated whether lymphocytes and neutrophils as predictors of inflammation. LHR and NHR along with MHR were good predictive biomarkers of inflammatory diseases such as metabolic syndrome [ 55 , 56 ]. In our study, we found no association between serum 25(OH)D and LHR and NHR.…”
Section: Discussionmentioning
confidence: 99%